Incorporating fossils into the Pinaceae tree of life. Issue 8 (9th August 2018) - Gernandt, David S.; Reséndiz Arias, Cecelic; Terrazas, Teresa; Aguirre Dugua, Xitlali; Willyard, Ann
Abstract : Premise of the Study: Pinaceae have a rich but enigmatic early fossil record, much of which is represented by permineralized seed cones. Our incomplete knowledge of morphology and anatomy in living and extinct species poses an important barrier to understanding their phylogenetic relationships and timing of diversification. Methods: We expanded a morphology matrix to 46 fossil and 31 extant Pinaceae species, mainly adding characters from stem and leaf anatomy and seed cones. Using parsimony and Bayesian inference, we compared phylogenetic relationships for extant taxa with and without fossils from the morphology matrix combined with an alignment of plastid gene sequences. Key Results: Combined analysis of morphological and molecular characters resulted in a phylogeny of extant Pinaceae that was robust at all nodes except those relating to the interrelationships of Pinus, Picea, and Cathaya and the position of Cedrus . Simultaneous analysis of all fossil and extant species did not result in changes in the relationships among the extant species but did greatly reduce branch support. We found that the placement of most fossils was sensitive to the method of phylogenetic reconstruction when analyzing them singly with the extant species. Conclusions: A robust phylogenetic hypothesis for the main lineages of Pinaceae is emerging. Most Early Cretaceous fossils are stem or crown lineages of Pinus, but close relationships also were found between fossils and several other extant genera. The phylogenetic position of fossils broadly supports the existence of extant genera in the Lower Cretaceous.